(untitled) (Elkom: Jurnal Elektronika dan Komputer, 2026)
The use of electrical energy in office environments that has not been optimally managed often results in waste, especially for lights and air conditioners that remain active outside of operating hours. This study aims to design and build an Internet of Things-based system using ESP32 to control office electricity with a time-based auto cut-off mechanism through a path after the Miniature Circuit Breaker. The system controls the load of lights and air conditioners concisely using relays as actuators, equipped with time synchronization via Network Time Protocol, Real Time Clock DS3231 as a backup time source when offline, DHT11 sensors, OLED displays, input buttons, and a Laravel-based web dashboard for two-way monitoring and control. The research method uses a design approach with stages of requirements analysis, hardware and software design, implementation, integration, and testing using black box testing, integration testing, and durability testing. The test results show that the system is able to activate and deactivate relays according to the operational schedule, distinguish workdays and national holidays, continue to run in conditions without internet, and provide an override mode for manual control. The developed system can support the efficiency of electrical energy use and the implementation of the Internet of Things-based smart office concept.